Domus Bolezlai : values and social identity in dynastic traditions of medieval Poland (c. 966-1138) - Wiszewski, Przemysław, 1974- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2010)
Between the middle of the 10th century and the middle of the 12th century both the cultural and the national identities of the Poles were formed. They were determined by political decisions made by the rulers from the Piast ruling house and built on a framework consisting of stories focused on the Piasts’ past. In all of this a dynastic tradition supported by the current ruler and his entourage was created and re-created. Tradition was understood as communication, the aim of which was to transmit values which define ways of perceiving the world by those people who accept this tradition as their own – by the Poles. The aim of the work is to seek traces of these traditions and values still alive in Polish culture.